The Effect of Laughter Therapy on Reducing Anxiety Level in Hypertension Patients - Purnamasari, Erna; Andhiyani, Arvina (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Degenerative diseases are chronic non-communicable diseases such as heart disease, hypertension, diabetes, obesity and others. One of the degenerative diseases is hypertension. Hypertension is referred to as the